Assessment of the attractiveness of foreign markets: A case study. Comparison of Armenia and Poland - Andranik Muradyan (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2018)
From the international marketing point of view, it is important to assess the attractiveness of the target country that can be interesting to foreign investors. It is worth analyzing all the possible opportunities and threats that may arise in each geographic market. It is also needed to assess the country's strengths and weaknesses and understand how these characteristic features can affect the company's growth perspectives. Each country has a specific political environment, socio-demographic features, economic situation, technological conditions, cultural identity, unique natural environment and legal rules. At the same time, there are regional and global geopolitical tendencies, common political structures, common economic conventions and elements of global culture. The specificity of the above-mentioned factors shapes a unique business environment that affects marketing strategies of entities that are planning to internationalize.This article will present a proposal of several criteria for assessing the attractiveness of foreign markets. These criteria will be selected because of their reliability and acceptability by various global institutions. This method can be used to estimate attractiveness of every country, but only two of them have been chosen for this article. Based on these indicators, the attractiveness of the Armenian market will be compared to Poland's attractiveness. The example of Poland in some areas because of its increasing attractiveness may be useful for Armenia and its government.
Keywords: M31; F21; G11; F62; 650; evaluation of foreign markets; assessment criteria; Armenia; geopolitical and economic problems; avoiding barriers